Seismic Frequency Analysis of Mount Tangkuban Parahu Using IoT-Based MPU6050 Sensor System - Almazari, Abar; Faradyba, Anggi; Akbar, Reyhan Nugraha; Sawita, Agus Sara; Evita, Maria; Djamal, Mitra (Indonesian Journal of Physics, 2025)
Indonesia is located at the convergence of three major tectonic plates—the Eurasian Plate, the Indo-Australian Plate, and the Pacific Plate—and lies within the Pacific Ring of Fire, making the country highly prone to seismic activity. Thus, seismic activity is one of the physical parameters used to define the status of a volcano. Consequently, the availability of affordable and accessible early earthquake detection systems is crucial to minimizing infrastructure damage and human casualties. One proposed solution involves the use of the MPU6050 sensor, which is capable of detecting ground acceleration. This sensor has been integrated and installed on a mobile robot for volcano monitoring, which was developed in previous research. In this study, the Fast Fourier Transform (FFT) is employed to convert ground acceleration data into ground frequency, which can then be used to assess seismic activity. Additionally, an ESP32 microcontroller is utilized to collect and process sensor data, which is automatically transmitted via a broker, allowing frequency data and seismic status to be visualized on a dashboard. This research aims to compare acceleration data collected in a laboratory setting (ITB campus) and in the field (Mount Tangkuban Parahu), measure ground vibration frequency at Mount Tangkuban Parahu, and determine the seismic activity status based on the ground vibration frequency at Mount Tangkuban Parahu.